2013
DOI: 10.1159/000350312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inulin-Type Fructans on Appetite, Energy Intake, and Body Weight in Children and Adults: Systematic Review of Randomized Controlled Trials

Abstract: Aim: To systematically evaluate the effects of inulin-type fructan (ITF) supplementation on appetite, energy intake, and body weight (BW) in children and adults. Methods: The MEDLINE, EMBASE, and Cochrane Library databases were searched up to December 2012 for randomized controlled trials (RCTs) that compared the effects of supplementation with well-defined ITF with placebo or no intervention. Results: For the pediatric population, 4 RCTs (n = 232) met the inclusion criteria. In infants, very limited evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 49 publications
1
45
0
3
Order By: Relevance
“…Similar results have been reported with oligofructose supplementation in a systematic review. 22 In our study, energy intake of the oligofructose-enriched inulin group was significantly decreased. The exact mechanism(s) of weight reduction by oligofructoseenriched inulin remains unclear.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Similar results have been reported with oligofructose supplementation in a systematic review. 22 In our study, energy intake of the oligofructose-enriched inulin group was significantly decreased. The exact mechanism(s) of weight reduction by oligofructoseenriched inulin remains unclear.…”
Section: Discussionsupporting
confidence: 45%
“…Some gut satiety hormones that is released as response to diet composition, including glucagon-like peptide-1 (GLP-1), Peptide YY (PYY), and ghrelin, are proposed for weight reduction. 22 In this study, we showed that oligofructose-enriched inulin supplementation for 8 weeks reduced FPG, HbA1c, TC, LDL-c, TC/ HDL-c ratio and LDL-c/ HDLc ratio, but could not significantly affect TG and HDL-c levels compared to maltodextrin group. Nassar and colleagues 7 reported that inulin resulted in significant decrease in serum glucose, insulin, insulin resistance, TC, TG, LDL-c and significant increase in HDL-c. Garcia and colleagues 23 reported that 5 weeks supplementation with inulin was resulted in 8% decrease in LDL-c. Bonsu and colleagues 24 did not find significant effect of inulin on serum lipid and serum glucose concentrations.…”
Section: Discussionmentioning
confidence: 56%
“…In this regard, Frost [25] showed that in mice, colonic acetate can cross the blood brain barrier and produce appetite suppression, at the level of the hypothalamus, in the absence of increased levels of PYY and GLP-1. A recent systematic review has been conducted of the effect of OF and inulin on appetite regulation, energy intake and weight loss in children and adults [26]. Studies amplifying this have been published by Cani et al [27,28] who showed that fructan prebiotics could influence satiety in humans.…”
Section: Prebiotics Obesity and Inflammationmentioning
confidence: 99%
“…Furthermore, OFS decreases food intake, fat mass development, and hepatic steatosis in normal and obese rodents [7,8,9,10,11,12,13]. In humans, contradictory results have been reported with inulin-type fructans on body weight reduction [14]. …”
Section: Introductionmentioning
confidence: 99%